Miya Improves Osteoarthritis Characteristics via the Gut-Muscle-Joint Axis According to Multi-Omics Analyses - Tianyang Xu; Dong Yang; Kaiyuan Liu; Qiuming Gao; Zhongchen Liu; Guodong Li (Frontiers Media S.A., 2022)
Background: The gut microbiota is associated with osteoarthritis (OA) progression. Miya (MY) is a product made from Clostridium butyricum, a member of gut microbiota. This study was conducted to investigate the effects of MY on OA and its underlying mechanisms.Methods: An OA rat model was established, and MY was used to treat the rats for 4 weeks. Knee joint samples from the rats were stained with hematoxylin-eosin, and fecal samples from the OA and OA+MY groups were subjected to 16S rDNA sequencing and metabolomic analysis. The contents of succinate dehydrogenase and muscle glycogen in the tibia muscle were determined, and related genes and proteins were detected using quantitative reverse transcription polymerase chain reaction and western blotting.Results: Hematoxylin and eosin staining showed that treatment with MY alleviated the symptoms of OA. According to the sequencing results, MY significantly increased the Chao1, Shannon, and Pielou evenness values compared to those in the untreated group. At the genus level, the abundances of Prevotella, Ruminococcus, Desulfovibrio, Shigella, Helicobacter, and Streptococcus were higher in the OA group, whereas Lactobacillus, Oscillospira, Clostridium, and Coprococcus were enriched after MY treatment. Metabolomic analysis revealed 395 differentially expressed metabolites. Additionally, MY treatment significantly increased the succinate dehydrogenase and muscle glycogen contents in the muscle caused by OA (p > 0.05). Finally, AMPK, Tfam, Myod, Ldh, Chrna1, Chrnd, Rapsyn, and Agrin were significantly downregulated in the muscles of OA mice, whereas Lcad, Mcad, and IL-1β were upregulated; MY significantly reversed these trends induced by OA.Conclusions: MY may promote the repair of joint damage and protect against OA via the gut-muscle-joint axis.